Investigating the Impact of Brief Outings on the Welfare of Dogs Living in US Shelters - Lisa M. Gunter; Rachel J. Gilchrist; Emily M. Blade; Rebecca T. Barber; Erica N. Feuerbacher; JoAnna M. Platzer; Clive D. L. Wynne (Animals, 2021)
Social isolation likely contributes to reduced welfare for shelter-living dogs. Several studies have established that time out of the kennel with a person can improve dogs’ behavior and reduce physiological measures of stress. This study assessed the effects of two-and-a-half-hour outings on the urinary cortisol levels and activity of dogs as they awaited adoption at four animal shelters. Dogs’ urine was collected before and after outings for cortisol:creatinine analysis, and accelerometer devices were used to measure dogs’ physical activity. In total, 164 dogs participated in this study, with 793 cortisol values and 3750 activity measures used in the statistical analyses. We found that dogs’ cortisol:creatinine ratios were significantly higher during the afternoon of the intervention but returned to pre-field trip levels the following day. Dogs’ minutes of low activity were significantly reduced, and high activity significantly increased during the outing. Although dogs’ cortisol and activity returned to baseline after the intervention, our findings suggest that short-term outings do not confer the same stress reduction benefits as previously shown with temporary fostering. Nevertheless, it is possible that these types of outing programs are beneficial to adoptions by increasing the visibility of dogs and should be further investigated to elucidate these effects.